A narrative feminist study of Jamaica Kincaid, the Autobiography of my Motherting, and mortgages on the financial crisis - Hadi Yasir, Hassan (Opción, 2020)
The aim of the study is to examine the term "feminist narration” and its essential characteristics in gender construction via comparative qualitative research methods. As a result, the significance of the investigation of the narrator helps in better understanding the account and in clearing up its narratological viewpoints. In conclusion, the examination through women's activist narratological approach clears up specific terms and capacities concerning the jobs played by the storyteller and the narrator in the female account content.